Temporal Resolution of Uncertainty and Recursive Models of Ambiguity Aversion - Strzalecki, Tomasz (Econometrica, 2013)
Dynamic models of ambiguity aversion are increasingly popular in applied work. This paper shows that there is a strong interdependence in such models between the ambiguity attitude and the preference for the timing of the resolution of uncertainty, as defined by the classic work of Kreps and Porteus (1978). The modeling choices made in the domain of ambiguity aversion influence the set of modeling choices available in the domain of timing attitudes. The main result is that the only model of ambiguity aversion that exhibits indifference to timing is the maxmin expected utility of Gilboa and Schmeidler (1989). This paper examines the structure of the timing nonindifference implied by the other commonly used models of ambiguity aversion. This paper also characterizes the indifference to long-run risk, a notion introduced by Duffie and Epstein (1992). The interdependence of ambiguity and timing that this paper identifies is of interest both conceptually and practically—especially for economists using these models in applications.